2023
DOI: 10.3389/fpls.2023.1046397
|View full text |Cite
|
Sign up to set email alerts
|

Selected indigenous drought tolerant rhizobium strains as promising biostimulants for common bean in Northern Spain

Abstract: Drought is the most detrimental abiotic stress in agriculture, limiting crop growth and yield and, currently, its risk is increasing due to climate change. Thereby, ensuring food security will be one of the greatest challenges of the agriculture in the nearest future, accordingly it is essential to look for sustainable strategies to cope the negative impact of drought on crops. Inoculation of pulses with biostimulants such as rhizobium strains with high nitrogen fixation efficiency and drought-tolerance, has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Similar effects were described in soybean (Sharaf et al, 2019) and common bean (Cytryn et al, 2007). Therefore, the rhizobia isolated in this work, that were able to nodulate under rainfed conditions, are probably efficient inocula under water stress conditions, as was demonstrated with some of them (del-Canto et al 2023). Thus, it would be interesting to test their efficiency under field conditions, following successful formulations such as those described by Pastor-Bueis et al (2019).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar effects were described in soybean (Sharaf et al, 2019) and common bean (Cytryn et al, 2007). Therefore, the rhizobia isolated in this work, that were able to nodulate under rainfed conditions, are probably efficient inocula under water stress conditions, as was demonstrated with some of them (del-Canto et al 2023). Thus, it would be interesting to test their efficiency under field conditions, following successful formulations such as those described by Pastor-Bueis et al (2019).…”
Section: Discussionsupporting
confidence: 85%
“…However, the number of nodules gives an idea of the abundance and/ or the viability of the rhizobia present soils, and it has also been stated that more drought-tolerant strains show higher nodulation capacity under drought conditions (Aulakh et al, 2020;del-Canto et al, 2023;Omari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the establishment of symbiotic relationships with efficient rhizobia can alleviate the effects of stress in legumes ( Igiehon et al., 2021 ; Omari et al., 2022 ; Oviya et al., 2023 ). This is the case of common bean, where it has been observed that symbiosis with drought-tolerant rhizobia improves plant tolerance to stress as well as legume yield and quality ( Steiner et al., 2020 ; Rodiño et al., 2021 ; del-Canto et al., 2023 ), even under field conditions ( Pastor-Bueis et al., 2019 ; Rodiño et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to different authors, the conservation of soil rhizobial diversity in agrosystems is a sustainable strategy of great interest to improve crop tolerance to stress by favouring the establishment of efficient symbiotic relationships even under water scarcity conditions ( Wolff and Killebrew, 2010 ; Szparaga et al., 2019 ; Hossain and Bakhsh, 2020 ). In addition to this, there is interest in the search for indigenous inocula that are better adapted to local growing conditions and therefore more efficient in responding to stress conditions ( del-Canto et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%